Perception of indoor air quality (IAQ) by workers in underground shopping centers in relation to sick-building syndrome (SBS) and store type: a cross-sectional study in Korea - Jeonghoon Kim; Mijung Jang; Kilyoung Choi; KyooSang Kim (BMC, 2019)
Abstract Background We examined the indoor air quality (IAQ) perceptions of workers and their relationships with the symptoms of sick-building syndrome (SBS) and store types in underground shopping centers. Methods In 2017, 314 store workers in nine underground shopping centers in Seoul, Korea, were assessed. The all participants' stores were partially opened onto a passage. Using questionnaires, they were asked about their demographics, job characteristics, 16 SBS symptoms, and seven IAQ perceptions. The SBS symptoms were categorized as skin, eye irritation, respiratory, or general. An IAQ perception score was calculated by adding the number of positive responses to each type of IAQ and categorized into three levels. Results The prevalence of SBS symptom groups in the previous month was 43.6% for skin symptoms, 62.4% for eye irritation symptoms, 65.6% for respiratory symptoms, and 64.7% for general symptoms. Participants who perceived IAQ were more likely to have SBS symptoms (odds ratio: 1.81-7.84). The type of store employing the workers was associated with several IAQ perceptions. Subjects who worked in clothing and fashion-accessory stores were more likely to have high IAQ perception scores than those who worked in food services. Conclusions About half of the store workers in underground shopping centers had experienced SBS symptom groups in the previous month. The SBS symptom groups were associated with almost all IAQ perceptions. Because IAQ perception was associated with store type, studies of IAQ in working areas might need to improve store workers' health in underground shopping centers.